2020
DOI: 10.3390/nu12010217
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Daily Low-Dose Date Consumption on Glycemic Control, Lipid Profile, and Quality of Life in Adults with Pre- and Type 2 Diabetes: A Randomized Controlled Trial

Abstract: Dates have a low glycemic index and are a source of antioxidants but, nevertheless, contain more than 70% sugar. This study aims to assess the effects of date consumption (three dates daily) on glycemic profile (HbA1c), body mass index (BMI), quality of life, and lipid profile, including total cholesterol, triglyceride, high-density lipoprotein (HDL), and low-density lipoprotein (LDL) in terms of safety for type 2 diabetic mellitus (T2DM) subjects. A randomized controlled trial was conducted with a sample of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…Previous studies have shown that good control of lipid profiles and glycemic levels can effectively prevent complications such as cardiovascular disease, diabetic nephropathy and diabetic retinopathy [ 1 , 2 ]. Lipid profiles referred to lipids in plasma, generally including triglyceride (TG), total cholesterol (TC), high density lipoprotein (HDL), and low density lipoprotein (LDL) clinically [ 3 ]. For patients with cardiovascular disease and T2D, lipid profiles should be strictly controlled to reduce mortality and complications [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that good control of lipid profiles and glycemic levels can effectively prevent complications such as cardiovascular disease, diabetic nephropathy and diabetic retinopathy [ 1 , 2 ]. Lipid profiles referred to lipids in plasma, generally including triglyceride (TG), total cholesterol (TC), high density lipoprotein (HDL), and low density lipoprotein (LDL) clinically [ 3 ]. For patients with cardiovascular disease and T2D, lipid profiles should be strictly controlled to reduce mortality and complications [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes mellitus is a progressive complex disease, and achieving normoglycemia is the first goal in patients with diabetes. On the way to achieving the target, it is necessary to increase the quality of life of the patients, reduce the complications and consider the comfort of the patient while performing this [1,2]. There are many oral and subcutaneous medications that provide these opportunities in the struggle against diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…The included studies approached 390 adult participants with diabetes mellitus, the duration of dates consumption ranged from one day to 12 weeks. In the present meta-analysis, all the included studies showed a reduction of fasting blood glucose, [17][18][19][20] odd ratio, -24.79, 95% CI=-34.75, -14.83 P =0.002. I 2 for heterogeneity=79%, P <0.00001, three studies were investigated the effects of dates fruit consumption on post-prandial blood glucose, all the studies showed a reducing effect, 17,19,21 2-4).…”
Section: Resultsmentioning
confidence: 95%
“…The current data showed that dates fruits reduce fasting plasma glucose with significant statistical difference [17][18][19][20] (odd ratio, -24.79, 95% CI=-34.75, -14.83 P =0.002. I 2 for heterogeneity=79%, P <0.00001).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation